Determinants of Catastrophic Health Expenditure (CHE): An Indonesian Family Life Survey (IFLS) 2007 & 2014 - Afanin Husna; Ni Made Sukartini (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study aims at finding and analyzing the determinants of catastrophic health expenditure (CHE) and its impact on the household economy in Indonesia, using pooled cross section data from IFLS 2007 and 2014. The study used binary logit regression for analyzing the determinants of CHE and OLS regression to see the impact of CHE on household economy. It was found that the occupational status of the head of household, size of the household, age, ownership of insurance, visits to health centers, location of residence, and the interaction variable of educated household heads with chronic disease affect the occurrences of CHE with various threshold. The OLS regression results found that households who experienced CHE with a threshold of 10% and 40% made a reduction in their basic needs (food expenditure). It implies that households that experienced CHE also experienced economic shocks and they are eventually forced to reduce their basic needs (food expenditure) to meet health needs.